Improving the Structural Characteristics of Heavy Concrete by Combined Disperse Reinforcement - Levon R. Mailyan; Alexey N. Beskopylny; Besarion Meskhi; Aleksandr V. Shilov; Sergey A. Stel’makh; Evgenii M. Shcherban’; Alla S. Smolyanichenko; Diana El’shaeva (Applied Sciences, 2021)
The development of perspective concrete mixes capable of resisting the action of external loads is an important scientific problem in the modern construction industry. This article presents a study of the influence of steel, basalt, and polypropylene fiber materials on concrete’s strength and deformation characteristics. A combination of various types of dispersed reinforcement is considered, and by methods of mathematical planning of the experiment, regression dependences of the strength and deformation characteristics on the combination of fibers and their volume fraction are obtained. It was shown that the increase in compressive strength was 35% in fiber-reinforced concretes made using a combination of steel and basalt fiber with a volume concentration of steel fiber of 2% and basalt fiber of 2%; tensile strength in bending increased by 79%, ultimate deformations during axial compression decreased by 52%, ultimate deformation under axial tension decreased by 39%, and elastic modulus increased by 33%. Similar results were obtained for other combinations of dispersed reinforcement. The studies carried out made it possible to determine the most effective combinations of fibers of various types of fibers with each other and their optimal volume concentration.